SEM PLS ANALYSIS OF TRAINING AND COMPETENCY OF EMPLOYEE QUALITY AND EMPLOYEE PRODUCTIVITY: CASE STUDY BANK NAGARI WEST SUMATERA - Yanti, Novi; Agussalim M; Shirley Atika Sari (Dinasti International Journal of Management Science, 2020)
This research aims to determine the effect of: 1) training and competence on the work quality of employees of Bank Nagari, West Sumatra directly. 2) training, competency and quality of work on the work productivity of Bank Nagari employees of West Sumatra directly. 3) training and competence through work quality on the work productivity of Bank Nagari employees of West Sumatera indirectly. The population is 295 people and the sample is 75 using the slovin formula. The analysis used is path analysis with SEM PLS data analysis techniques. The results showed a positive and significant influence of job training variables on work productivity, competence on work quality and work quality on work productivity. Whereas indirectly job training has no influence on work productivity. However, competence has an influence on work productivity through direct work quality. The results of the coefficient of determination analysis (R2) of 0.231 and 0,361, which means that training and competence for work quality and work productivity are 23,1% and 36,1%.